Establishing and implementing best practice to reduce unplanned admissions in those aged 85 years and over through system change [Establishing System Change for Admissions of People 85+ (ESCAPE 85+)]: a mixed-methods case study approach - Andrew Wilson; Richard Baker; John Bankart; Jay Banerjee; Ran Bhamra; Simon Conroy; Stoyan Kurtev; Kay Phelps; Emma Regen; Stephen Rogers; Justin Waring (National Institute for Health Research, 2015)
Background: In England, between 2007/8 and 2009/10, the rate of unplanned hospital admissions of people aged 85 years and above rose from 48 to 52 per 100. There was substantial variation, with some areas showing a much faster rate of increase and others showing a decline. Objectives: To identify system characteristics associated with higher and lower increases in unplanned admission rates in those aged 85 years and over; to develop recommendations to inform providers and commissioners; and to investigate the challenges of starting to implement these recommendations. Design: Mixed-methods study using routinely collected data, in-depth interviews and focus groups. Data were analysed using the framework approach, with themes following McKinsey's 7S model. Recommendations derived from our findings were refined and prioritised through respondent validation and consultation with the project steering group. The process of beginning to implement these recommendations was examined in one 'implementation site'. Participants: Six study sites were selected based on admission data for patients aged 85 years and above from primary care trusts: three where rates of increase were among the most rapid and three where they had slowed down or declined. Each 'improving' or 'deteriorating' site comprised an acute hospital trust, its linked primary care trust/clinical commissioning group, the provider of community health services, and adult social care. At each site, representatives from these organisations at strategic and operational levels, as well as representatives of patient groups, were interviewed to understand how policies had been developed and implemented. A total of 142 respondents were interviewed. Results: Between 2007/8 and 2009/10, average admission rates for people aged 85 years and over rose by 5.5% annually in deteriorating sites and fell by 1% annually in improving sites. During the period under examination, the population aged 85 years and over in deteriorating sites increased by 3.4%, compared with 1.3% in improving sites. In deteriorating sites, there were problems with general practitioner access, pressures on emergency departments and a lack of community-based alternatives to admission. However, the most striking difference between improving and deteriorating sites was not the presence or absence of specific services, but the extent to which integration within and between types of service had been achieved. There were also overwhelming differences in leadership, culture and strategic development at the system level. The final list of recommendations emphasises the importance of issues such as maximising integration of services, strategic leadership and adopting a system-wide approach to reconfiguration. Conclusions: Rising admission rates for older people were seen in places where several parts of the system were under strain. Places which had stemmed the rising tide of admissions had done so through strong, stable leadership, a shared vision and strategy, and common values across the system. Future work: Research on individual components of care for older people needs to take account of their impact on the system as a whole. Areas where more evidence is needed include the impact of improving access and continuity in primary care, the optimal capacity for intermediate care and how the frail elderly can best be managed in emergency departments. Study registration: UK Clinical Reasearch Network 12960. Funding details: The National Institute for Health Research Health Services and Delivery Research programme.